Laser Therapy for Peyronie’s Disease: A Randomized Control Double-Blind Pilot Study - Allameh, Farzad; Razzaghi, Mohammadreza; Rayegani, Seyed Mansoor; fallahkarkan, morteza; Ranjbar, Arash; Rahavian, Amirhosein; Javadi, Atefeh; Ghiasy, Saleh; Razzaghi, Zahra (Journal of Lasers in Medical Sciences, 2019)
Introduction: The management of Peyronie’s disease (PD) has remained a therapeutic dilemma for physicians and there is no gold standard treatment. In this paper, we decided to investigate the beneficial effect of the intralesional administration of verapamil compared with the intralesional administration of verapamil plus a low-intensity laser (LIL). Methods: Research was activated from May 2016 to May 2018 and a total of 38 men aged 18 years and older completed the investigation. The subjects were randomly divided into 2 groups. Group 1 was composed of 22 patients that were treated only by verapamil (5 mg) plus a sham laser weekly for 6 weeks, and group 2 consisted of 22 patients that received a laser, using the BTL – 6000 HIGH-INTENSITY LASER 12 W machine and the same protocol of intralesional verapamil injection. The visual analogue scale (VAS) was used to evaluate pain during an erection, penile ultrasonography was used to measure plaque size, the penile curvature angle degree was measured using the photographs taken during an erection, and the International Index of Erectile Function questionnaire was used to assess erectile function. The follow-up treatment lasted for nine months, with visits performed in the 3rd and 9th months. Results: All study parameters decreased significantly after treatment in both arms, but the reduction in pain and penile curvature improvements in combination therapy revealed more significant changes in 3 months (p = .035, p=.032). Nevertheless, these improvements were not seen in the follow-up session after 9 months. Conclusion: A laser appears to be safe treatment modality in carefully-selected patients with PD. It has moderate efficacy in the short term.